NOT MYSELF: ANTI-SURVIELLANCE AESTHETICS AND THE CHIN- DOWN SELFIE - Shorey, Samantha (AoIR Selected Papers of Internet Research, 2015)
Photographs are often thought to be a record of reality. Rather than being a representation, they seem to depict the subject with accuracy, acting as evidence of that particular moment in time. Yet, there are limits to what photography can tell us or teach us, for there will always be something — a whole life even — outside the frame. For users of the platform Tumblr, these limits become tools for $2 online spaces of privacy and self disclosure. Advancing camera technology and the inescapability of social media have given us new (or perhaps transformed) methods of representation, and an increased expectancy for one to do so. This is perhaps most visually evident in the recent proliferation of self portrait photos: the selfie. Yet, as digital photography provides tools for new forms of exposure, the users of this technology also create new kinds of privacy. The proposed paper looks to a specific selfie sub-genre, the chin-down selfie, and asks what photos taken in this way can tell us about the conflicting, often ambivalent, relationship digital media users have with self disclosure. In dialogues with literature on privacy and surveillance, this research is informed by a series of qualitative focus groups with college-age, female Tumblr users. Drawing on the methods of visual cultural studies, I argue that the chin-down selfie is part of a larger cultural concern over who is watching us and at what consequence.